Barbados : meeting the challenge of competitiveness in the 21st century - Rojas-Suárez, Liliana (Inter-American Development Bank WashingtonUS, 2006)
Examines the strengths and competiveness challenges facing Barbados from the points of view of the institutional and private sector constraints and environment for competitiveness, labour market conditions and trade policy framework and performance. Looks at the tourism industry and includes a brief analysis which focuses on the agriculture sector.